Rancangan Perbaikan Kualitas Toko Sepatu West Store Medan Berdasarkan Pendekatan Servqual dan QFD - Agung Akhirullah; Uun Novalia Harahap; Muhammad Fazri (CV. IRA PUBLISHING, 2023)
Business disciplines, which include production, sales, supply of goods, and services, are the main factors in doing business, especially for customers. If a company creates various things that can be handled and can be seen in a tangible form, then these services do not have a form but can be felt by customers. This should not be underestimated by business people, especially if the company is engaged in the service sector. In a service-providing manufacturing business, quality is one of the various elements that must be considered, if the business has a competitive nature against competitors. Quality is considered crucial because it proves the product being sold, not only by assessing the use or service but also by the suitability between buyers and users in utilizing the goods or services provided and selected. If the products and services offered have quality, the level of consumer desire is increasing, this is called the provision of good service quality. This research is quantitative research using Servqual and QFD methods, this research was conducted by the author at the West Store Medan Shoe Store, to know and analyze the level of customer satisfaction with the quality of service and goods in the West Store Medan store. In this study, the researcher describes each method, the goal is that the validity of the data generated is not in doubt. This study shows that there is still a lack of service at the West Store Medan Shoe Store, including the lack of responsiveness of store employees in responding to buyers, being less responsible when serving, parking and cleanliness are still lacking, to the lack of complete facilities.